FRI0492 Clinical characteristics of parenchymal neuro-behcet's disease: a retrospective analysis. (12th June 2018) - Yan, D.; Liu, J.; Wu, D.; Peng, L.; Liu, Z.; Zheng, W.
Abstract : Background: Neurological involvement is one of the most serious complications in Behcet's disease (BD). Objectives: To investigate the clinical characteristics of parenchymal neuro-Behcet's Disease (pNBD). Methods: We retrospectively reviewed all the medical records of BD patients who were admitted to our institute between 2000 and 2016. The diagnosis of NBD was based on the 2014 International Consensus criteria for NBD. 1 Eighty-four BD patients without neurological involvement were randomly matched by sex and age as control. Results: 42 patients (25 male and 17 female) with pNBD accounted for 4.2% of the 1009 hospitalised BD patients during that period. The mean age at BD onset and at neurological onset was (30.1±11.1 years old and (35.3±12.1 years old, respectively. The majority of patients developed neurological symptoms after other initial systemic symptoms of BD in a median period of 2 months (range from 0–49). Neurological onset was concomitant with the onset of BD in 6 cases (14.3%). The most frequent location was brainstem (23/42, 54.8%). Spinal cord involvement was presented in five cases, in which four with cervical cord involved. 13 cases suffered from multiple lesions. Pyramidal (21/42, 50.0%) and headache (14/42, 33.3%) were the most common manifestations of pNBD. Lumbar puncture was performed in 40 patients, in which 80% (32/40) of patients had normal pressure and 55% (22/40) had elevated protein levels ((0.51±0.24) g/L). Compared with the controls, the prevelance of ocular involvement (uveitis, retinal vasculitis, scleritis) was significantly higher in pNBD (35.7%) (p=0.041, OR=2.36, 95%CI=1.03–5.44) (table 1). Cranial MRI in 32 patients showed the lesions were mainly in the midline structures, including brainstem (22/42, 52.4%), periventricular (13/42, 31.0%), centrum semiovale (8/42, 19.0%). Typically, the lesions were in hypersignal in T2. All pNBD patients recevied corticosteroids (≥1 mg/kg/d) and 23 patients (54.8%) received the pulse dose (1 g/d). Cyclophosphamide was the most commonly used immunosuppressant (39/42) and 10 cases took more than one immunosuppressants (including methotrexate and azathioprine). Biological agents were administrated in six refractory pNBD patients, including Infliximab in 4 cases, Tocilizumab in 1 case, and Interferon-α2a in 1 case. Intrathecally injection of dexamethasone 10 mg and methotrexate 10 mg was given to 28 patients. With a median follow-up of 28 months (4 to 156 months), 22 patients (52.4%) achieved clinical improvements, while 10 patients (23.8%) relapsed and 4 patients died (the mortality was 9.5%). Six patients lost to follow up. Conclusions: The parenchymal neurological involvement is a rare complication of BD with a high mortality. Its most frequent location is brainstem. Ocular involvement is a risk factor for pNBD. Early identification and active treatment are vital for a good prognosis. References: [1] Kalra S, Silman A, Akman-Demir G, et al. Diagnosis and management of Neuro-Behçet's disease: international consensus recommendations. J Neurol. 2014Sep;261(9):1662–76. Disclosure of Interest: None declared